The Effect of ROA, DER, CR, and Firm Size on Firm Value with Sales Growth Moderation in Indonesia (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to evaluate the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio on Firm Value, with Sales Growth as a moderator variable, in textile and garment companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The population of this study consisted of 21 companies, and purposive sampling was used to select 19 companies according to the established criteria. The analytical method used was panel data regression analysis with the help of Eviews version 12.0. The results of this study indicate that Return on Assets (ROA) has a negative and significant effect on firm value, Debt to Equity Ratio (DER) and Firm Size have a positive and significant effect on firm value, Current Ratio (CR) does not have a significant effect on firm value, and Sales Growth cannot moderate the effect of Return on Assets on firm value. The condition of ROA that has a negative effect on firm value can describe a situation where the greater the company's profit in the form of assets, the lower the company's value will be, or conversely, the higher the company's value, the lower the company's assets will be.